Pembinaan Santri Pondok Pesantren Minhajusshobirin Untuk Penerapan Cara Produksi Pangan Olahan yang Baik Pada Produksi Minuman Belimbing Wuluh Rendah Kalori - Novi Yantih; Faizatun, Faizatun; Djamil, Ratna; Qodriah, Rahmatul; Zaidan, Sarah (SULUH: Jurnal Abdimas, 2023)
Abstract The students at the Minhajusshobirin Islamic Boarding School have produced a wuluh start fruit drink. Their drink has a high sugar content, so it cannot be consumed by diabetics. In addition, the product has not been certified, so it cannot be marketed widely. The purpose of this Community Service Program is to provide training for students to 1) Improve the skills of the students in good processed food production methods (good manufacturing practices/GMP), especially in producing wuluh star fruit drinks, 2) Increase the competitiveness of wuluh star fruit drink products by using sweeteners, low calories using stevia, and 3) Product stability test facilitation. The methods used in this activity included: licensing, surveys, counselling, training, laboratory testing, coaching, monitoring-evaluation, and publication of activity results. Measuring tools to assess the increase in knowledge and skills of students in the application of GMP in making low-calorie drinks are through questionnaires and direct surveys, as well as through product stability tests according to SNI 3719: 2014 standards in the QLab laboratory of the Faculty of Pharmacy, Universitas Pancasila. Training and supervision on GMP for processed food on sanitation and hygiene parameters have been given by a team of lecturers from the Faculty of Pharmacy, Universitas Pancasila. The quality assessment of the low-calorie drinks produced can be seen from the increase in product stability time of the test results in the laboratory. The pre-test and post-test results showed an increase in student understanding by 18.24%, which can be concluded that the training was effective. This activity is expected to be useful as an entrepreneurial provision for students when they serve in the community. Keywords: Universitas Pancasila, GMP, wuluh starfruit